The predictive value of coronary microvascular dysfunction for left ventricular reverse remodelling in dilated cardiomyopathy - Kan, Ao; Leng, Yinping; Li, Shuhao; Lin, Fang; Fang, Qimin; Tao, Xinwei; Hu, Mengyao; Gong, Lianggeng (Frontiers in Cardiovascular Medicine, 2023)
Abstract Aims: To evaluate the degree of coronary microvascular dysfunction (CMD) in dilated cardiomyopathy (DCM) patients by cardiac magnetic resonance (CMR) first-pass perfusion parameters and to examine the correlation between myocardial perfusion and left ventricle reverse remodelling (LVRR). Methods: In this study, 94 DCM patients and 35 healthy controls matched for age and sex were included. Myocardial perfusion parameters, including upslope, time to maximum signal intensity (Timemax), maximum signal intensity (SImax), baseline signal intensity (SIbaseline), and the difference between maximum and baseline signal intensity (SImax-baseline) were measured. Additionally, left ventricular (LV) structure, function parameters, and late gadolinium enhancement (LGE) were also recorded. The parameters were compared between healthy controls and DCM patients. Univariable and multivariable logistic regression analyses were used to determine the predictors of LVRR. Results: With a median follow-up period of 12 months [interquartile range (IQR), 8-13], 41 DCM patients (44%) achieved LVRR. Compared with healthy controls, DCM patients presented CMD with reduced upslope, SIbaseline, and increased Timemax (all p < 0.01). Timemax, SImax, and SImax-baseline were further decreased in LVRR than non-LVRR group (Timemax: 60.35 [IQR, 51.46-74.71] vs. 72.41 [IQR, 59.68-97.70], p=0.017; SImax: 723.52 [IQR, 209.76-909.27] vs. 810.92 [IQR, 581.30-996.89], p=0.049; SImax-baseline: 462.99 [IQR, 152.25-580.43] vs. 551.13 [IQR, 402.57-675.36], p=0.038). In the analysis of multivariate logistic regression, Timemax [odds ratio (OR) 0.98; 95% confidence interval (CI) 0.95-1.00; p=0.032)], heart rate (OR 1.04; 95% CI 1.01-1.08; p=0.029), LV remodelling index (OR 1.73; 95% CI 1.06-3.00; p=0.038) and LGE extent (OR 0.85; 95% CI 0.73-0.96; p=0.021) were independent predictors of LVRR. Conclusions: CMD could be found in DCM patients and was more impaired in patients with non-LVRR than LVRR patients. Timemax at baseline was an independent predictor of LVRR in DCM.